Family Planning in Patients With ADPKD–Results From the DIPAK Consortium - Willemijn A.L. Vrijlandt; Thomas Bais; Lisa Margot Vijn-Villalever; Stefan P. Berger; Esther Meijer; Ron T. Gansevoort; Margriet F.C. de Jong; J.P.H. Drenth; J.W. de Fijter; D.J.M. Peters; M. Salih; E.J. Hoorn; et al. (Kidney International Reports)
Introduction: Autosomal dominant polycystic kidney disease (ADPKD) can impact family planning because it can result in reduced fertility, increased risks of adverse pregnancy outcomes, and a 50% inheritance risk. This study explored considerations of people with ADPKD regarding family planning. Methods: This prospective cohort study included patients from the “Developing Intervention Strategies to Halt Progression of ADPKD (DIPAK) observational study. We analyzed patient demographics, disease characteristics, and reproductive outcomes. Patients with children were grouped by whether ADPKD influenced their family size, with a specific focus on females. Childless patients were categorized as voluntarily or involuntarily childless, within a subgroup of nonsingle individuals over 27 years. Univariable and multivariable regression were conducted to identify characteristics of patients dissatisfied with their family size. Results: Among 696 patients (60% female), 462 (66%) had children. Of these, 35 (12%) reported that ADPKD had influenced their desired family size. Among childless individuals, 16 (23%) were involuntarily childless. Those reporting the influence of ADPKD on family size were more often female, had hypertensive pregnancy complications, and a Mayo classification class D or E. Involuntarily childless patients were more likely to report reduced fertility, be older, and have a family member with end-stage kidney disease (ESKD). Conclusion: Women with ADPKD were significantly more likely than men to report that ADPKD influenced their family size. Disease severity and pregnancy complications were associated with perceived influence. These results highlight the need for physicians to consider factors affecting family planning and to provide comprehensive counselling on reproductive health and genetic testing options.